淬火油中含水的危害、检测和对策 - 陈春怀; 周敬恩 (Jixie chuandong)
Containing water in quenching oil not only affects its normal performance but exerts danger of fire. The harmfulness, however, has not been received enough attention. This paper firstly analyses its bad impact with the use of cooling curve, then introduces quality and qualitative analysis respectively toward the water content in oil. After the identification of possible source for water in the oil, the counter measures for contained water are offered.